Making Los Angeles home : the integration of Mexican immigrants in the United States - Alarcón, Rafael; Escala-Rabadan, Luis, 1959-; Odgers, Olga (University of California Press, 2016)
"Making Los Angeles Home examines the different integration strategies implemented by Mexican immigrants in the Los Angeles region. Relying on statistical data and ethnographic information, the authors analyze four different dimensions of the immigrant integration process (economic, social, cultural, and political) and show that there is no single path for its achievement, but instead an array of strategies that yield different results. However, their analysis also shows that immigrants' successful integration essentially depends upon their legal status and long residence in the region. The book shows that, despite this finding, immigrants nevertheless decide to settle in Los Angeles, the place where they have made their homes"--Provided by publisher
Keywords: Mexicans -- California -- Los Angeles -- Social conditions.; Mexican Americans -- California -- Los Angeles -- Social conditions.; Immigrants -- California -- Los Angeles -- Social conditions.; Social integration -- California -- Los Angeles.; Los Angeles (Calif.) -- Emigration and immigration -- Social aspects.; Mexico -- Emigration and immigration -- Social aspects.; Mexicains -- Californie -- Los Angeles -- Conditions sociales.; Américains d'origine mexicaine -- Californie -- Los Angeles -- Conditions sociales.; Intégration sociale -- Californie -- Los Angeles.; SOCIAL SCIENCE -- Discrimination & Race Relations.; SOCIAL SCIENCE -- Minority Studies.; SOCIAL SCIENCE -- Sociology -- General.; Emigration and immigration -- Social aspects; Immigrants -- Social conditions; Mexican Americans -- Social conditions; Mexicans -- Social conditions; Social integration; California -- Los Angeles; Mexico